2014
DOI: 10.1007/s12041-014-0420-x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and introgression of QTL for yield and related traits in two backcross populations derived from Oryza sativa cv. Swarna and two accessions of O. nivara

Abstract: Advanced backcross QTL (AB-QTL) analysis was carried out in two Oryza nivara-derived BC2F2 populations. For nine traits, we identified 28 QTL in population 1 and 26 QTL in population 2. The two most significant yield-enhancing QTL, yldp9.1 and yldp2.1 showed an additive effect of 16 and 7 g per plant in population 1, while yld2.1 and yld11.1 showed an additive effect of 11 and 10 g per plant in population 2. At least one O. nivara-derived QTL with a phenotypic variance of >15% was detected for seven traits in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Thus, these loci are worthy for use when improving grain size and weight of 'Kasalath', and other rice varieties with small grain size, by marker-assisted selection and are also important in QTL pyramiding programs. The results of these pleiotropic QTLs are consistent with the corresponding traits reported in previous publications (Swamy et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, these loci are worthy for use when improving grain size and weight of 'Kasalath', and other rice varieties with small grain size, by marker-assisted selection and are also important in QTL pyramiding programs. The results of these pleiotropic QTLs are consistent with the corresponding traits reported in previous publications (Swamy et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…The negative relationship between PE and GW may suggest that lower grain yield is directly derived from the scarcity of SNP companied by a longer PE. Previous studies have found several QTLs for highly correlated traits located on the same or on neighboring chromosomal intervals, possibly resulting from pleiotropism or multigenic effects (Marathi et al, 2012;Swamy et al, 2014). In the present study, four QTL clusters were located on four intervals: RM5389-RM6407, RM1347-RM341, RM6080-RM6832, and RM3628-RM412 on chromosomes 1, 2, 3, and 6, respectively (Figure 2).…”
Section: Discussionsupporting
confidence: 65%
“…Thus, some agronomically important traits of O. nivara are more similar to those of cultivated rice49. In a previous study, several significant yield-enhancing QTLs from O. nivara were identified by advanced backcross (BC 2 F 2 ) QTL analysis21. In the present study, by combining a high-density bin map with phenotypic data from ILs, O .…”
Section: Discussionmentioning
confidence: 55%
“…Some valuable genes from O . nivara , such as those for yield components, grain quality, and grassy stunt virus resistance have been transferred into cultivated rice and widely employed in rice production2021454647. However, owing to the overall inferior performance of O .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation